Effect of different chelating agents and their surface tension on the amount of apically extruded debris - Hakan Gokturk; Ismail Ozkocak; Ugur Aydin; Emine Demir Serefli (Elsevier, 2021)
Background/purpose: During root canal preparation apical extrusion is an undesirable situation that can cause postoperative complications. The aim of the present study is to evaluate the effect of the presence of different chelators in root canals during preparation on the amount of apically extruded debris and to investigate the effect of surface tension of irrigant on the apical extrusion. Materials and methods: Ninety extracted mandibular incisor teeth were included. Prior to canal preparation, the teeth were mounted to Eppendorf tubes. Root canals of the samples were prepared with Reciproc instruments in the presence of different chelating agents (17% EDTA-liquid, 17% EDTA-gel, 7% maleic acid, 2.25% peracetic acid, 10% citric acid) and 5% NaOCl. Apically extruded debris was collected in Eppendorf tubes and weighted with an electronic balance. The surface tension of solutions was calculated with the ring method using a du Noüy ring digital tensiometer. The statistical analysis was performed with Tamhane's T2 test for apical extrusion and the Tukey for surface tension. The correlation between apical extrusion and surface tension was compared using Pearson's coefficient. Results: The least amount of apically extruded debris was with EDTA-gel, peracetic acid and citric acid which were similar to each other. NaOCl had the highest surface tension whereas peracetic acid and EDTA-liquid had the lowest. There was no significant correlation exists between apical extrusion and surface tension. Conclusion: The presence of EDTA-gel, citric acid and peracetic acid in root canals during preparation decreased the amount of apically extruded debris compared to other solutions. The investigated irrigation solutions have no significant effect on the amount of apical debris extrusion.